2020
DOI: 10.1590/s1517-707620200002.1020
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion failures of austenitic and duplex stainless steels in a biodiesel plant

Abstract: The neutralization of catalysts with hydrochloric acid is an important step in a biodiesel process which generates steel corrosion due to the decrease in pH, and the addition of chlorides in the medium. Other factor responsible for corrosion and consequently failures is the poor miscibility between biodiesel and acid water generating a heterogeneous coverage of the surface of the pipelines and equipment by biodiesel and acid water, presence of galvanic cells and localized corrosion. In this paper, corrosion fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Knowing the possible corrosion risks, researches have pin-pointed the metal category and mechanisms, as reported in Table 3. As expected, stainless (304-316) have shown the highest corrosion resistance by most chemically induced aversion phenomena [44].…”
Section: The Microbial Effectsupporting
confidence: 72%
See 2 more Smart Citations
“…Knowing the possible corrosion risks, researches have pin-pointed the metal category and mechanisms, as reported in Table 3. As expected, stainless (304-316) have shown the highest corrosion resistance by most chemically induced aversion phenomena [44].…”
Section: The Microbial Effectsupporting
confidence: 72%
“…The studies on corrosion behaviour of aluminium and its alloys are mentioned in The corrosion rate of mild carbon steel is known to be 12-13.5 times faster in biofuels than in most fossil diesels [56]. High quantity of oxygen and moistures in biofuels drastically increases the corrosion susceptibility of iron and steels; facilitates the formation of galvanic cells and localised corrosion [44]; forms corrosion products such as FeO(OH) (product of redox reaction between Fe, O 2 and H 2 O) [57], Fe 2 O 2 CO 3 (product of CO 2 solution in biofuels causing reaction between H 2 CO 3 and FeO(OH)) [58], FeCO 3 (product of RCOO − carboxylate radicals reaction with Fe radicals) [59], Fe(OH) 3 (final product of FeO(OH) reaction with dissolved H 2 O) [19] and Fe 2 O 3 (product of direct oxidation of iron with highly moist and oxygenated biofuels) [42]. The high concentration of α-FeOOH, β-FeOOH, δ-FeOOH and Fe 2 O 2 CO 3 are reported as corrosion byproducts for most iron-based materials.…”
Section: Production: Biorefinerymentioning
confidence: 99%
See 1 more Smart Citation
“…Torres, Santos and Lins [75] investigated a biodiesel plant's pipeline in Brazil in order to establish why the plant had failed during its operation. After a thorough analysis it was found that production halts without proper acid phase drainage, an inefficient configuration of the neutralisation current insertion spool in the biodiesel stream, and a high concentration of the catalyst were the causes of the failures.…”
Section: Operation Key Performance Indicator (𝑶 𝒊 )mentioning
confidence: 99%
“…Heating these steels to temperatures of 600º to 850°C leads to a reduction in ferrite content () and to the formation of the sigma phase (), a very common intermetallic compound that has a greater effect on the mechanical properties of the material and significantly reduces ductility and notched impact strength. It forms preferentially at the interface between ferrite and austenite, which is stable up to a maximum temperature of 1050°C [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%